'I am a paramount chief, this land belongs to my ancestors': the reconfiguration of rural authority after Zimbabwe's land reforms. (22nd August 2016) - Mkodzongi, Grasian
Abstract : This article explores the reconfiguration of rural authority in the aftermath of Zimbabwe's Fast Track Land Reform Programme, particularly the way the programme has allowed local chiefs to deploy ancestral autochthony as a way of contesting state hegemony over the countryside. It argues that chiefs cannot simply be viewed as undemocratic remnants of colonial rule; instead, a nuanced understanding of their role in rural governance is required.